Key Determinants of Chinese Direct Investment in Central and Eastern Europe - Belvončíková, Barbora; Janíčko, Martin, 1983-; Rod, Aleš; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2016)
Chinese outward direct investment is surging and is unique in the sense that its development is much faster than of any other developing country. This thesis investigates the determinants of Chinese outward direct investment (ODI) in eight countries of Central and Eastern Europe throughout the years 2003-2014. Using panel data analysis, the regression model incorporates both traditional macroeconomic variables as well as institutional variables, testing thereby what are Chinese ODI driven by in those post-communist countries. The quality of institutional framework is represented by EBRD indicators, which seem to be more suitable for transition economies. Findings suggest that Chinese MNEs do not access Central and Eastern European countries primarily for market-seeking reasons, however the fact of being a member of the EU boosts Chinese ODI, since entering a member state market grants at the same time access to the whole EU common market and this fact is decisive for China. Also, R&D capacities play an important role in attracting Chinese ODI. On the other hand, Chinese ODI seem not to be associated with a good institutional environment of a host country, only large-scale privatization index is found significant and positively correlated with Chinese ODI inflow. Therefore, the findings of this thesis lead to the conclusion that macroeconomic factors are still more influential than the institutional ones when studying Chinese outward direct investment in Central and Eastern Europe.
Vedoucí práce: Martin Janíčko
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2016
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2016
Způsob přístupu: Internet
Keywords: ekonomie [obor bakal. práce]; bakalářské práce; bachelor's theses